2001
DOI: 10.1046/j.1525-139x.2001.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Dialysis Catheters

Abstract: Acute dialysis catheters are non-cuffed, non-tunnelled catheters used for immediate vascular access. They are primarily used for acute renal failure in bed-bound patients and for short-term use in patients with malfunction of permanent access. Long-term use of acute catheters is not recommended, but does occur with acceptable infection rates in dialysis centers where tunnelled, cuffed catheters are not available. Most acute catheters are made of polyurethane, but silicone catheters are now available with large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 21 publications
2
45
0
1
Order By: Relevance
“…This approach is commonly used by nephrologists in patients with acute renal failure, or patients with temporary loss of permanent access. 8 Studies of CVC placement have documented the use of femoral access and the low incidence of associated complications. [9][10][11] The femoral site has several anatomic advantages over the subclavian or jugular approach that reduces the insertion-related complications: the anatomy is easily learned, the arterial pulse provides a reliable handmark for insertion, and haemostasis can be achieved by direct compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is commonly used by nephrologists in patients with acute renal failure, or patients with temporary loss of permanent access. 8 Studies of CVC placement have documented the use of femoral access and the low incidence of associated complications. [9][10][11] The femoral site has several anatomic advantages over the subclavian or jugular approach that reduces the insertion-related complications: the anatomy is easily learned, the arterial pulse provides a reliable handmark for insertion, and haemostasis can be achieved by direct compression.…”
Section: Discussionmentioning
confidence: 99%
“…7 Femoral vein catheterization is an attractive method to obtain central venous access because it is associated with a low complication rate during insertion, but its use has traditionally been discouraged due to the high incidence of infection or thromboembolic complications. [8][9][10] Although the femoral vein is a frequently used central access for hemodialysis, there are scant data in the setting of leukapheresis. We present our experience using shortterm dialysis catheters placed in the femoral vein for venous access during PBSC collection.…”
mentioning
confidence: 99%
“…Variability in access patency, infection rates, and mortality among types of hemodialysis accesses is well established, with AVF being superior to AVG in all three of these outcome measures and tunneled catheter being the most inferior. [9][10][11][12][13] The National Kidney Foundation Kidney Disease Outcome Quality Initiative guidelines and the Fistula First Breakthrough Initiative are a result of these observations. [14][15][16] Although data are limited in this area, it seems unlikely that variability in outcomes of type of access explains the mortality differences seen between different ethnic groups because AfricanAmerican hemodialysis patients have been found to have a lower prevalence of AVF than do non-Hispanic white hemodialysis patients.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…Earlier studies reported that subclavian vein stenosis occurs in 15% to 50% of chronic hemodialysis patients [118] . Therefore, the CDC guidelines recommend (Category ⅠA) [44] that acute hemodialysis catheters have to be inserted in the IJV or FV due to the increased possibility of thrombosis and stenosis for catheters inserted into the SV [119] . In the authors' opinion, the risk of venous stenosis after subclavian inserted lines is mostly related to the size of the catheter and to the possible occurrence of a catheter-related thrombosis of the SV (since the stenosis is often the final fibrotic consequence of a severe occlusive thrombosis with only partial recanalization).…”
Section: Hemodialysis Cathetersmentioning
confidence: 99%